Analyzing Humor in Newspaper Comic Strips Using Verbal-Visual Analysis - Fallianda, Fallianda; Astiti, Rani Yuni; Hanim, Zulvy Alivia (Lingua Cultura, 2018)
The researchers aimed at analyzing the meaning of humor in newspaper comic strips within a variety of incongruous combinations of multimodal rhetoric. The current research focused on how humor was produced via verbal medium only, via both verbal and visual media, as well as via visual only. The source of data was 74 political comic strips featured in Kompas newspaper. The General Theory of Verbal Humor (GTVH) was adapted as a framework of analysis. The analysis of the data confirms the following categorization: 49 humors appear only in text, 22 humor result from the interaction of text and image, and three humor come from images. In addition, humor which appears in text only and cases of the interaction between the two semiotic modes (either complementary or contradictory) is based on puns, exaggerations, contradictions, analogies, parallelisms, or verbal metaphors. Special attention is given to humor produced by the interaction of both text and image and by the images only which cause the hyperdetermination of humor, which can produce two or more humorous utterances. Meanwhile, the humor appeared in visual comic strips is produced exclusively by the visual language of knowledge resources.